Quantum Curve and the First Painlevé Equation - Iwaki, K.; Saenz, A. (Symmetry, Integrability and Geometry: Methods and Applications, 2016)
We show that the topological recursion for the (semi-classical) spectral curve of the first Painlevé equation PI gives a WKB solution for the isomonodromy problem for PI. In other words, the isomonodromy system is a quantum curve in the sense of [Dumitrescu O., Mulase M., Lett. Math. Phys. 104 (2014), 635-671, arXiv:1310.6022] and [Dumitrescu O., Mulase M., arXiv:1411.1023].